INVESTIGATION OF A SINUSOIDALY SUPPLIED TRANSFORMER UNDER LINEAR AND NON-LINEAR LOADING CONDITIONS - Taci, M. Salih; Sarul, M. Hadi (IEEE, 2008)
This paper investigates the effects of harmonics on core and windings of a sinusoidal supplied transformer for two different loading conditions: linear and nonlinear. When harmonics exist, transformer variables, such as core resistance current, magnetic inductance current and excitation current, become non-sinusoidal. This means that the core resistance and magnetic inductance shows nonlinearity under harmonics conditions. In addition, core loss (P-fe), magnetizing reactance reactive power loss (Q(xm)), primary and secondary windings resistance power losses (P-cu1, P-cu2) and primary leakage reactance power losses (Q(cu1), Q(cu2)) can be obtained. In effects, these nonlinear variations lead to extra power loss and currents in transformer, which should be taken into account during transformer design.
Keywords: Transformer; linear load; nonlinear load; harmonics; Computer Science; Engineering; Telecommunications